Analyzing decision making Metric conjoint analysis. - Louviere, Jordan J. (Quantitative applications in the social sciences ;, 1988)
This volume introduces the theory, method, and applications of one type of conjoint analysis technique. These techniques are used to study individual judgement and decision processes and forecast the chosen behavior of individuals or the populations they represent.